Pendekatan Kerangka Kebijakan Naratif untuk Memelihara Toleransi Beragama dalam Kerangka Kebijakan di Kota Cilegon - Imam Rozikin; Ermaya Suradinata; Deti Mulyati; Mansyur Achmad (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
Religion continues to be a critical domain in Indonesian public life, but its governance remains fraught with contestation, especially at the local level. This study analyzes how dominant and counter-narratives influence the implementation of religious pluralism policies in Indonesia, focusing on the conflict surrounding the HKBP Maranatha Church in Cilegon. Applying the Narrative Policy Framework (NPF), it maps how policy actors construct, reinforce, and contest narratives surrounding the enforcement of Joint Regulation No. 9/8 of 2006. The findings show that historical, legal-administrative, and human rights narratives compete to frame the conflict, with exclusionary narratives dominating through outdated decrees, social pressure, and policy ambiguity. In contrast, counter-narratives advanced by civil society and minority groups seek recognition and justice. The study reveals that legal vagueness and weak national oversight enable institutionalized discrimination. It recommends regulatory revision, institutional strengthening, and the cultivation of inclusive narratives to promote equitable religious governance. The study’s limitations include its localized and temporal focus, suggesting the need for comparative or longitudinal research in future studies across different regions. This research contributes conceptually to narrative-based policy studies and empirically to religious governance debates in plural societies.